Food52 dynamite chicken : 60 never-boring recipes for your favorite bird - Kord, Tyler (Ten Speed Press, 2019)
Sautéed, fried, or nestled in a sheet pan, chicken is a clear winner for home cooks around the world--from jerk chicken and chicken adobo to Vietnamese chicken noodle soup, pho ga. But because chicken is so popular, you may feel like you've run out of new ways to love it. That's where Food52 and Tyler Kord come in, bringing you a clever collection of deliciously inventive chicken dishes. In this book, you'll find creative recipes for every occasion: Winning weeknight dinners and ambitious-but-worth-it weekend projects; meals to impress guests and satisfy picky kids; and cozy comfort foods to curl up with. Tyler's new classics will soon join your regular recipe lineup, with dishes like Roast Chicken with All of the Vegetables in Your CSA, Broiled Chicken Thighs with Plum Tomatoes & Garlic, Patrick's Fried Chicken with Spicy Pickles, and Tangy Rose's Lime-Glazed Wings. He throws in a few surprises, too, like Chicken & Kimchi Pierogies and Spicy Parmesan Chicken Potpie, along with an ingenious combination of chicken and lasagna (called Chickensagna, naturally). And thanks to handy how-tos on carving, trussing, spatchcocking, making stock from scratch, and much more, you'll learn every chicken trick in the--well--book. So even if chicken's already your trusty dinner go-to, Dynamite Chicken will have you eating lots more of it, and never getting bored.